Early Care: Resources and Opportunities for Psychological and Pedagogical Support for a Child and his Family in the Yaroslavl Region - Rusanova, L.S. (Autizm i narušenie razvitiâ, 2024)
Objectives. Timely and properly organized comprehensive care for young children is able to prevent the appearance of secondary deviations in child development and ensure the effectiveness of corrective and developmental impact. The results of a monitoring that was organized in the Yaroslavl region of the Russian Federation to assess the need of families in childhood early care activities for the correction and prevention of possible disorders are analyzed and summarized. The organization of activities to provide early psychological and pedagogical assistance to children and their families is presented. Methods. 956 families with young children living in the Yaroslavl region took part in the survey. The age of the parents is from 23 to 37 years old. During the monitoring, the activities of basic organizations for the provision of psychological and pedagogical assistance to children from birth to three years old were studied, according to the following indicators: the quantitative and nosological representation of young children, the psychological and pedagogical support of young children and their parents, staffing in basic organizations providing early help services. Results. In 2023, early help was provided to 1174 children and their families in 140 early help services established in the regional education system, in 2022, early care was provided to 1235 children of the target group, which may be due to a slight decrease in the birth rate in the Yaroslavl region. According to the data of the psychological, medical and pedagogical commissions, 2,598 children from birth to three years old underwent a comprehensive examination in 2023, which is 24% more than the number of young children examined in 2022. Comprehensive psychological, medical and pedagogical support of young children is provided by 460 specialists of various profiles. In the process of psychological and pedagogical support, 1,283 events were held with young children and their parents. Conclusions. The study reflects that the difficulties of providing early care in educational organizations are due to the interdepartmental fragmentation of early care institutions, the insufficient implementation of the practice of home visits, accompanying a child in natural life situations, and the low representation of medical workers in the early care system. The factors contributing to the improvement of the results of psychological and pedagogical support of a child with disabilities and his family have been established: interdisciplinarity in the organization of early care; support of the child in natural life conditions; screening-diagnostics; remote counseling. Актуальность и цель. Своевременная и правильно организованная комплексная помощь детям раннего возраста помогает предупредить появление вторичных отклонений и обеспечить эффективность коррекционно-развивающего воздействия. Проведен анализ и обобщение результатов мониторинга, организованного в Ярославском регионе Российской Федерации с целью оценки потребности семей в мероприятиях по ранней помощи детям для коррекции и предупреждения возможных нарушений. Представлена организация деятельности по оказанию ранней психолого-педагогической помощи детям и их семьям. Методы и методики. В анкетировании участвовали 956 семей, имеющих детей раннего возраста и проживающих в Ярославской области (ЯО). Возраст родителей от 23-х до 37-ми лет. В ходе мониторинга изучалась деятельность базовых организаций ЯО по оказанию психолого-педагогической помощи детям от рождения до трех лет: численная и нозологическая представленность детей раннего возраста; психолого-педагогическое сопровождение детей и их родителей; кадровое обеспечение в базовых организациях, оказывающих услуги ранней помощи. Результаты. В 2023 году ранняя помощь оказана 1174-м детям и их семьям в 140 службах ранней помощи, созданных в региональной системе образования. По данным психолого-медико-педагогических комиссий, в 2023 году прошли комплексное обследование 2598 детей от рождения до 3-х лет, что на 24% больше, чем в 2022 году. Комплексное психолого-медико-педагогическое сопровождение детей раннего возраста осуществляют 460 специалистов разного профиля: педагоги-психологи, учителя-дефектологи, учителя-логопеды, инструкторы по физической культуре, социальные педагоги, врачи-педиатры. В процессе психолого-педагогического сопровождения проведено 1283 мероприятия с детьми раннего возраста и их родителями. Выводы. Результаты мониторинга показывают, что трудности оказания ранней помощи в организациях сферы образования обусловлены межведомственной разобщенностью учреждений ранней помощи; недостаточной реализацией практики домашнего визитирования и сопровождения ребенка в естественных жизненных ситуациях; низкой представленностью в системе ранней помощи медицинских услуг. Установлены факторы, способствующие улучшению результатов психолого-педагогического сопровождения ребенка с ограниченными возможностями здоровья и его семьи: междисциплинарность в организации ранней помощи; сопровождение ребенка в естественных жизненных условиях; скрининг-диагностика; дистанционное консультирование.